2018
DOI: 10.1007/s40090-018-0154-3
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on the inhibitive effect of Crataegus oxyacantha and Prunus avium plant leaf extracts on the corrosion of mild steel in hydrochloric acid solution

Abstract: The inhibitive action of plant leaf extracts, Crataegus oxyacantha (Hawthorn) and Prunus Avium (Sweet Cherry) on the corrosion of mild steel in 0.5 M HCl solution was investigated using open circuit potential-time measurements (OCP), potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) techniques. Functional groups of these plants' leaf extracts and their absorption bands were identified by Fourier transform infrared spectroscopy (FTIR) and Ultra-Violet Spectrophotometer (UV), respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…The extensive use of mild steel in the construction of petroleum refineries tanks, flow lines and transmission pipelines is as a result of ease of its fabrication and low cost [1]. At the other side, acid media are widely applied in the metallurgical industry for pickling and descaling of metals, chemical or electrochemical processes in oil refinery, and deactivation of equipment in atomic power establishment [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extensive use of mild steel in the construction of petroleum refineries tanks, flow lines and transmission pipelines is as a result of ease of its fabrication and low cost [1]. At the other side, acid media are widely applied in the metallurgical industry for pickling and descaling of metals, chemical or electrochemical processes in oil refinery, and deactivation of equipment in atomic power establishment [2].…”
Section: Introductionmentioning
confidence: 99%
“…For solving the resulting corrosion problems for mild steel in acid environment in oil and gas industries, use of corrosion inhibitors is the best practical and cost-effective way. When added to an acidic environment in small amounts, inhibitors can appreciably reduce corrosion rates [1][2][3]. It has already been found that organic compounds which contain either lone pair-donating heteroatoms like N, O, S and P, or structural moieties with -electrons that interact with metal, demonstrate good inhibitive properties [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…The increase of publication shows an exponential trend. Just in the past 2018, numerous naturally occurring products such as Nettle leaves [26], Red Algae Halopitys Incurvus [27], Prosopis juliflora [28], Barley Agro-Industrial Waste [29], Matricaria recutita chamomile [30], Rollinia occidentalis [31], Glycyrrhiza glabra leaves [32], Holoptele integrifolia leaf [33], Ginkgo leaf [34], Centaurea cyanus [35], Crataegus oxyacantha and Prunus avium plant [36], Pongamia Pinnata [37], Sida Cordifolia [38], Allium sativum (garlic extract) [39], Raphanus Sativus L. [40], Borago officinalis L. [41], Cuscuta reflexa [42], Mature areca nut husk [43], Pisum sativum peels [44], grape pomace [45][46][47], Artemisia Judaica Herbs [48], and Opuntia Ficus-Indica [49] have been evaluated as potential corrosion inhibitors. The increase in interest in green inhibitors has stroked the eager of many researchers round the globe to search for natural plant based inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Table 3 summarizes the main attributions found for each material (EPE, QF and QEPE).For all the spectra, the band between 3600-3200cm -1 indicates the presence of -OH group from water molecules, and the peaks around 2960cm -1 are attributed to C-H stretching in organic compounds. 16 For EPE spectrum (Figure 2a), the absorption band of C=C bond in the ring (1576-1560cm -1 ) indicates the presence of aromatic group in the extract. The peaks around 1200-1000cm -1 are attributed to C-O-bond in alcohol and ethers.…”
Section: Resultsmentioning
confidence: 99%